Perancangan Konten Video Dokumenter Thrive Motorcycle Dengan Pendekatan Teori Visual Metaphor - Pandega Putra (Wimba : Jurnal Komunikasi Visual, 2021)
The growth of creative industry in Indonesia is currently increasing from time to time. This is also supported by information media that is reach its users easily. These factors affect the pattern of trend alteration that occur in society, in this case is Custom Culture trend, a trend that comes from the past and defined as a lifestyle that emphasizes self-expression and identified in various kinds of daily objects that they used. One of the example is transportation, in this case a motorcycle. The perpetrators of this trend use vehicles that match their character or make modifications according to what they want. Starting from that phenomenon, there are many modification service provides who try to fullfill these needs. Thrive Motorcycle is one of the many workshops that have a vision and are well known to foreign countries. Although it has been recognized by the international scene, Thrive Motorcycle is not yet known to the wider community. An informative video content can strengthen Thrive Motorcyle's presence in the creative industry more further. In order to create a work that fits the identity of Thrive Motorcycle, an approach is taken through the theory of Visual Metaphor which can be applied in cinematography and message delivery aspects. This theoretical approach will create a video content with unique character but still communicative. This design process uses qualitative methods by conducting interviews with the research subjects and literature studies as a basis for analysis in determining the desired visual. The results of this design can be used as an alternative communication pattern that can be used in the process of designing documentary video content.